Hodnoty acidobazické rovnováhy krve nĕkterých druhů domácích zvírat - Komárek, J; Stros, K; Sýkora, I; Kynclová, I; Jadrný, L; Selinger, P (Veterinarni medicina, 1976)
By means of the Astrup equilibration method the values of the acid-base balance of the blood were determined in 104 cows, 99 horses, 100 pigs, 15 sheep, 20 goats, and in 101 dogs. The pH values of the blood, the partial pressure of CO2, the base excess, the base buffer, the standard bicarbonate, the actual bicarbonate, and the total CO2 were processed statistically and are presented in tables.
Keywords: parciální tlak; Partial Pressure; psi; ovce; koncentrace vodíkových iontů; Carbon Dioxide; hydrogenuhličitany; Dogs; Animals, Domestic; skot; Horses; oxid uhličitý; Swine; hospodářská zvířata; Acid-Base Equilibrium; zvířata; acidobazická rovnováha; Hydrogen-Ion Concentration; Bicarbonates; koně; Cattle; Goats; prasata; Sheep; kozy; Animals